Cross-Diffusion Effect on Mixed Convective Fluid Flow through Horizontal Annulus - Muli, Charles N.; .Kwanza, Jackson K (Mathematical Theory and Modeling, 2014)
The unsteady mixed convective fluid flow through an annulus filled with a fluid-saturated porous medium is numerically investigated in this study in the presence of Cross-Diffusion effect and constant Heat Source. The flow configuration and coordinate system for an annulus which is horizontal position have been considered Details of the effect of several parameters controlling the velocity, temperature and concentration profiles are shown graphically and the observations are discussed. These parameters include the Non-Darcy parameter, Pressure gradient, Soret effect, Schmidt Number, Dufour effect, Eckert number and Prandtl Number. The effect of these dimensionless parameters mentioned above is observed either to enhance, to decrease or have no effect on the velocity, temperature and the concentration profiles.
Keywords: Unsteady Flow; Cross-Diffusion effect; Constant heat source Effect